PROSES FABRIKASI KOMPONEN WALKING BEAM PADA NEW PUMPING UNIT - Bayu Andika Wijaya; Nurul Iman Supardi; Putra Bismantolo (UNIB Press, 2026)
The oil and gas eguipment business unit is engaged in the manufacture of pumping units, in its production process, oil and gas equipment is required to run as effectively and efficiently as possible so that it can produce high quality products. In the process of making a pumping unit there are several processes, one of which is the fabrication of the walking beam. This report describes the fabrication process of the walking beam component for the new pumping unit. The study aims to thoroughly understand the stages of production, the operation of the main machines, and the obstacles that arise during the fabrication process. The production process begins with component design using CAD software, followed by cutting ASTM A36 steel material with a CNC flame cutting machine, tack welding with an H-Beam assembling machine, and main welding using an H-Beam gantry welding mMachine. The next stage includes straightening process with H-Beam flange straightening machine, shot blasting to clean the surface, and final painting to inhibit corrosion. This study also identified several factors inhibiting production, such as delays in material supply that affect the smoothness of the cutting process, and instability of the nozzle position during the tack welding process, which requires repeat work. Recommendations provided include improving the material management system to ensure timely availability of raw materials and the use of more stable nozzle holders to improve welding accuracy. This report is expected to be a guide to improve the efficiency and quality of component fabrication processes in the manufacturing industry, especially in the oil and gas equipment sector.